PENGEMBANGAN SISTEM INFORMASI PENGOLAHAN PAJAK PADA BIDANG PAJAK DAERAH HOTEL DAN RESTAURANT DI DINAS PENDAPATAN DAERAH KOTA BANDUNG - Yelli Eka Sumadhinata (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
From beginning autonomy region now, every region must have to develop ability get source income region for expenditure APBD and which one with use maximum tax assignment region. For then needed a new system development to encode for processing on computer tax region and to increase service towards public. This research intend for knowing everything about excellent foundation income tax region and how to processing data from obligation tax report, when tax obligation from they tax and doing registration, fill up SPTPD after processing will persistent value tax region must pay for hotel and restaurant. Afterwards SPTPD to encode for processing on computer then result data mold form SKPD. Mold SKPD will give to obligation tax and can do payment with bring SKPD for get SSPD all of them will encode for processing with use language program Borland Delphi version 7.0 and for save database use SQL SERVER 2000. Result this research showed that system working as of precisely comply with a request service public, however a lot of tax obligation feel decrease concept mechanism reporting, process and pay for tax obligation until enthusiastic society community less.